2014
DOI: 10.1016/j.neuron.2014.07.027
|View full text |Cite|
|
Sign up to set email alerts
|

TNF and Increased Intracellular Iron Alter Macrophage Polarization to a Detrimental M1 Phenotype in the Injured Spinal Cord

Abstract: Macrophages and microglia can be polarized along a continuum toward a detrimental (M1) or a beneficial (M2) state in the injured CNS. Although phagocytosis of myelin in vitro promotes M2 polarization, macrophage/microglia in the injured spinal cord retain a predominantly M1 state that is detrimental to recovery. We have identified two factors that underlie this skewing toward M1 polarization in the injured CNS. We show that TNF prevents phagocytosis-mediated conversion from M1 to M2 cells in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
472
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(489 citation statements)
references
References 77 publications
(101 reference statements)
16
472
0
1
Order By: Relevance
“…Previous reports describe that microglia and macrophages express predominantly M1 markers for the first 2 weeks after SCI, whereas the expression of M2 signatures is scarce (Kigerl et al 2009;Kroner et al 2014). Here we first extended these observations using fluorescence-activated cell sorting analysis (FACS) to assess the temporal changes in expression of M1 (iNOS and CD16/32) and M2 (Arg1 and CD206) markers in microglia and macrophages for the first 4 weeks after spinal cord contusion injury in mice.…”
Section: Microglia and Macrophages Do Not Acquire Anti-inflammatory Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports describe that microglia and macrophages express predominantly M1 markers for the first 2 weeks after SCI, whereas the expression of M2 signatures is scarce (Kigerl et al 2009;Kroner et al 2014). Here we first extended these observations using fluorescence-activated cell sorting analysis (FACS) to assess the temporal changes in expression of M1 (iNOS and CD16/32) and M2 (Arg1 and CD206) markers in microglia and macrophages for the first 4 weeks after spinal cord contusion injury in mice.…”
Section: Microglia and Macrophages Do Not Acquire Anti-inflammatory Pmentioning
confidence: 99%
“…Microglia and macrophages display a predominantly pro-inflammatory/M1-like phenotype after SCI (Kigerl et al 2009;Kroner et al 2014). However, there is currently limited information about the factors that prevent these cells from acquiring a pro-repair M2-like phenotype after SCI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the expression of iron metabolism‐related proteins in M2 macrophages is different than that in M1 macrophages 1. Another study12, 13 showed that increasing levels of intracellular iron induced polarization of proinflammation macrophages. The results of these studies suggest that regulating iron concentration in macrophages may be a novel and effective strategy for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%